Storytelling to Improve Students’ Speaking Skill - Zuhriyah, Mukminatus (English Education: Jurnal Tadris Bahasa Inggris, 2017)
Speaking is the first way to interact with others in the social community. Furthermore, the success in learning a language at first can be seen from the ability of the learner’s speaking. However, it is very hard for the beginners to speak the foreign language, especially English. There are a lot of reasons why they get difficulties in speaking, such as lack of ideas to tell, lack of vocabularies to express the ideas, lack of the chance to speak, and lack of the interesting teaching method that can motivate them to speak. Thus, this research applied storytelling in speaking class in order that the beginners are eager to speak English. This research was a collaborative classroom action research whose main purpose was to know whether or not storytelling could improve the students’ speaking skill. Meanwhile, the specific purposes consisted of describing: (1) the lecturer’s activities, (2) the students’ activities, and (3) the students’ responses when storytelling was applied in the speaking class. The subjects were 23 students of class N of the second semester of Intensive English Program of Hasyim Asy’ari University (UNHASY) Tebuireng Jombang in the academic year of 2016/2017. The data of this research were got from the observations done by the collaborator and the speaking test. The result showed that there was an improvement on students’ speaking skill after the implementation of storytelling. The speaking test result in cycle two explained that the students’ speaking aspects got good progress. Storytelling improved their comprehension, fluency, vocabulary, grammar, and pronunciation. Thus, it can be said that storytelling could improve students’ speaking skill.